Prognostic Value of EEG in Neonatal Meningitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The value of an EEG performed soon (first week) after onset of neonatal bacterial meningitis in the prediction of adverse outcome at 1-19 year follow-up (mean, 4 yrs) was evaluated in 37 of 101 infants admitted and diagnosed with meningitis at the Hospital for Sick Children, Toronto, Canada.